Paraschistura makranensis, a new loach from the Jegin River drainage in southern Iran with comments on P. ilamensis and P. pasatigris (Teleostei: Nemacheilidae) - Eagderi, Soheil; Mousavi-Sabet, Hamed; Freyhof, Jörg (Zootaxa, 2019)
Paraschistura makranensis, new species, is described from the Jegin River drainage in southern Iran. It is distinguished from its congeners in Iran by having a plain brown or slightly mottled colour pattern on the flanks, a very slender body with a relatively short head, a complete lateral line extending almost to the caudal-fin base, the caudal peduncle covered by scales, and a suborbital flap in males. Paraschistura makranensis is distinguished from P. bampurensis and P. hormuzensis, its closest relatives in our dataset, by an uncorrected-pairwise distance based on the COI data of 4.0 and 5.4%, respectively. We treat Paraschistura pasatigris as a synonym of P. ilamensis.